Peripheral schwannomas of the tibial nerve: surgical results in a case series - Andreani, Lorenzo; Ipponi, Edoardo; Ruinato, Alfio Damiano; Falcinelli, Federico; De Franco, Silvia; D'Arienzo, Antonio; Capanna, Rodolfo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Schwannomas of the lower limb are uncommon benign tumors and those arising from Tibial Nerve are particularly rare. We report our experience on the topic, with particular attention to clinical presentation and lower limbs overall functionality before and after treatment. Our aim is to assess clinical impairment caused by the tumor and evaluate the effectiveness of surgical treatment.Materials and methods: Time between symptoms outbreak and diagnosis, as well as pre- operative tumor size were evaluated for each case. Pre-operative and post-operative overall lower limb functionality were assessed using both MSTS and LEFS scores. Sensitive symptoms and muscular strength were also evaluated before and after surgery. Results: 7 patients were included in our study. The mean follow-up was 22.9 months. Average diagnostic delay was 8 months and tumor size was 29.3mm. Before surgery each patient had positive Hoffmann-Tinel sign and an at least mild paresthesia, 57% of our cases had slight reduction of muscular strength. Pre-operative MSTS score was 24.4 and LEFS score was 64.7. Tumor size and diagnostic delay were associated with pre-operative functionality. No major local complication was recorded during or after surgery. Each patient with pre-operative sensitive or motorial deficit benefited the effects of surgical treatment. Conclusions: Our cases suggest early diagnosis could reduce the impact of the disease on patients’ activities of daily living and quality of life. Surgery, for its part, represents a safe and reliable approach to Tibial Nerve schwannomas with good chances of clinical and functional remission.